THE INFLUENCE OF GROUP COUNSELING USING SELF-MANAGEMENT TECHNIQUES ON STUDENTS' SELF-CONCEPT - Rahmad Fardiamsyah; Dimas Ardika Miftah Farid (Nurul Jadid University, 2024)
This study investigates the impact of group counseling using self-management techniques on students' self-concept. Students with low levels of self-concept often encounter various developmental obstacles such as teenage acquaintances, procrastination, and drastic mood changes, which can lead to personal disturbances. These issues can be addressed effectively through self-management techniques in a group counseling setting. Self-concept refers to an individual's perception of themselves, shaped by their experiences and interactions with the world. The purpose of this research is to determine the effect of group counseling using self-management strategies on students' self-concept. The study employs a quantitative methodology without the use of a control or comparison group, utilizing a one-group pre-test post-test design with a single experimental class. The Wilcoxon test was conducted, yielding asymptotic statistical results. The findings indicate that the hypothesis (Ha) is accepted, demonstrating a significant difference between pre-test and post-test scores, specifically an increase in post-test scores compared to pre-test scores. The sig (2-tailed) value is 0.042. Therefore, it can be concluded that group counseling using self-management strategies significantly influences the self-concept of students.